Classification of European and Mediterranean coastal dune vegetation. Issue 3 (17th May 2018) - Marcenò, Corrado; Guarino, Riccardo; Loidi, Javier; Herrera, Mercedes; Isermann, Maike; Knollová, Ilona; Tichý, Lubomír; Tzonev, Rossen T.; Acosta, Alicia Teresa Rosario; FitzPatrick, Úna; Iakushenko, Dmytro; Janssen, John A. M.; et al.
Abstract: Aims: Although many phytosociological studies have provided detailed local and regional descriptions of coastal dune vegetation, a unified classification of this vegetation in Europe and the Mediterranean Basin has been missing. Our aim is to produce a formalized classification of this vegetation and to identify the main factors driving its plant species composition at a continental scale. Location: Atlantic and Baltic coasts of Europe, Mediterranean Basin and the Black Sea region. Methods: We compiled a database of 30, 759 plots of coastal vegetation, which were resampled to reduce unbalanced sampling effort, obtaining a data set of 11, 769 plots. We classified these plots with TWINSPAN, interpreted the resulting clusters and used them for developing formal definitions of phytosociological alliances of coastal dune vegetation, which were included in an expert system for automatic vegetation classification. We related the alliances to climatic factors and described their biogeographic features and their position in the coastal vegetation zonation. We examined and visualized the floristic relationships among these alliances by means of DCA ordination. Results: We defined 18 alliances of coastal dune vegetation, including the newly described Centaureo cuneifoliae‐Verbascion pinnatifidi from the Aegean region. The main factors underlying the differentiation of these alliances were biogeographic and macroclimatic contrasts between the Atlantic–Baltic, Mediterranean and Black Sea regions, along with ecological differences between shifting and stable dunes. The main difference in species composition was between the Atlantic–Baltic and Mediterranean–Black Sea regions. Within the former region, the main difference was driven by the different ecological conditions between shifting and stable dunes, whereas within the latter, the main difference was biogeographic between the Mediterranean and the Black Sea. Conclusions: The first formal classification of the European coastal dune vegetation was established, accompanied by an expert system containing the formal definitions of alliances, which can be applied to new data sets. The new classification system critically revised the previous concepts and integrated them into a consistent framework, which reflects the main gradients in species composition driven by biogeographic influences, macroclimate and the position of the sites in the coast–inland zonation of the dune systems. A revision of the class concept used in EuroVegChecklist is also proposed. Abstract : The first formal classification of the European coastal dune vegetation was established, accompanied by an expert system containing the formal definitions of alliances. The new classification critically revised the previous concepts and integrated them into a consistent framework which reflects the main gradients in species composition driven by biogeographical influences of the dune systems.